The art of human rights: enriching the life of the law school through drawings and other visual resource (Prudentia Iuris, 2019)
In the life of the Law School, focus on the “visual” can operate at three differentlevels: learning, teaching, and examining (legal concepts). My main interestin this paper is to explore the latter level, “examining”, broadly considered so as toencompass evaluation in general. Furthermore, that interest is pinned down hereto the area of constitutional rights and human rights in general, even though theconclusions reached can (and should) likely be extrapolated to other areas of the law.